1991
DOI: 10.1073/pnas.88.24.11227
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent differences in the profile of mutations induced by an ultimate carcinogen from benzo[a]pyrene.

Abstract: Mutations in the coding region of the hypoxanthine (guanine) phosphoribosyltransferase (HPRT) gene of Chinese hamster V-79 cells were examined after exposure ofthe cells to a high cytotoxic dose (0.48 pM; 35% survival) and a low noncytotoxic dose (0.04 ,M; 100% survival) of the ultimate carcinogen (+)-7R,8S-dihydroxy-9S, 10R-epoxy-7,8,9,10-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 18 publications
5
68
0
Order By: Relevance
“…The second possibility is favored because p53-dependent MFR was observed at low doses but not at high doses of CPBA, a result hard to reconcile with a requirement for a threshold of DNA damage to obtain p53-dependent MFR. In addition, there are dose-dependent di erences in the pro®le of BPDEinduced mutations in the hprt gene of V79 cells (Wei et al, 1991(Wei et al, , 1993, suggesting dose-dependent di erences in the type of BPDE-induced DNA damage. Furthermore, it is certainly not unreasonable to suspect the existence of (dose-dependent) di erences in the type of damage caused by diverse DNA-damaging agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second possibility is favored because p53-dependent MFR was observed at low doses but not at high doses of CPBA, a result hard to reconcile with a requirement for a threshold of DNA damage to obtain p53-dependent MFR. In addition, there are dose-dependent di erences in the pro®le of BPDEinduced mutations in the hprt gene of V79 cells (Wei et al, 1991(Wei et al, , 1993, suggesting dose-dependent di erences in the type of BPDE-induced DNA damage. Furthermore, it is certainly not unreasonable to suspect the existence of (dose-dependent) di erences in the type of damage caused by diverse DNA-damaging agents.…”
Section: Discussionmentioning
confidence: 99%
“…AFB1 and BPDE are well-studied genotoxic carcinogens that are known to cause point mutations (Foster et al, 1983;Trottier et al, 1992b;Levy et al, 1992;Yang et al, 1987;Wei et al, 1991Wei et al, , 1993. Although CPBA is a known DNA-damaging agent (Jacobsen and Humayun, 1986;Rosenthal et al, 1990), its mutagenic properties seem not to have been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneous distribution of mutations is the combined result of the initial adduct distribution and adduct removal by DNA repair processes. Recent results have shown that adduct recognition and the rate of adduct removal depend on the bases surrounding the adducted base (Hess et al 1997;Wei et al 1993Wei et al , 1994.…”
Section: Benzo[a]pyrene (Bp) (+)-Bp-78-epoxide (-)-Bp-78-dihydrodiomentioning
confidence: 99%
“…Although possible under certain circumstances, the realistic potential for such a mechanism can be questioned (2). To begin with, cancer is a progressive disease, in which somatic cells undergo a series of genetic alterations which culminate in a neoplasm that exhibits multiple gene defects in those genes controlling cell proliferation, cell behavior, and genomic stability (ie, oncogenes, tumor suppressor genes) (4,17,48 (32), which perhaps accounts for the fact that mutagenesis (40,41) and oncogene activation (1,19) (23), which indicates the existence of no-effect levels (NELs) for DNA damage in some tissues. A particularly compelling example of this is provided by the EDo, study of 2-acetylaminofluorene (AAF) in mice, a study that revealed an apparent NEL for urinary bladder neoplasms (6,7), although in this study and in a major study on diethylnitrosamine (DEN) in rats (26,27), the exposure response for liver neoplasms was considered to be linear, with no NEL.…”
Section: Introductionmentioning
confidence: 99%